Anticipating the downturn: business cycle forecasting for veterinary practice strategy in the United States - Neill, Clinton L.; Salois, Matt; McKay, Charlotte (Frontiers in Veterinary Science, 2025)
IntroductionVeterinary medicine is often considered recession-resistant, yet little empirical analysis has evaluated the industry’s distinct economic cycle. This study addresses this gap by modeling and forecasting the veterinary medicine business cycle.MethodsTime series econometric techniques were applied to inflation-adjusted consumer price index (CPI) and expenditure data from 2000 to 2025. Dynamic autoregressive integrated moving average (ARIMA) models, incorporating macroeconomic indicators—industrial production, real disposable income, and consumer sentiment—were used to estimate and forecast monthly trends in CPI and real expenditures.ResultsForecasts reveal a continuing increase in veterinary service prices but a deceleration in real expenditures, indicating the industry entered a recessionary phase in late 2024. Prediction intervals suggest persistent negative growth through mid-2026, though with a potential for recovery toward the end of the forecast horizon.DiscussionThese results demonstrate an industry-specific business cycle that does not necessarily mirror the macroeconomy. The veterinary industry’s current downturn presents both operational risks and strategic opportunities for practices, particularly in cost containment, workforce planning, and service innovation.